2017
DOI: 10.1007/s10639-017-9605-2
|View full text |Cite
|
Sign up to set email alerts
|

The value of using ICT in the education of school students with learning difficulties

Abstract: This article argues that whatever the 2015 OECD report says about the value of ICT in relation to PISA results, our research has shown that using ICT in the education of students with Learning Difficulties has great value in interesting, enthusing and inspiring these students, so leading to better educational outcomes. The term 'Learning Difficulties' (LD) is used to refer to a condition of a large group of children who need extra assistance with schooling and arises from a vast range of cognitive and physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…The papers showed a certain amount of heterogeneity in their definition of LDs. Some authors proposed a specific definition ( Chen et al, 2015 ; Richardson, 2015 ; Shonfeld and Ronen, 2015 ; Straub and Vasquez, 2015 ; Benmarrakchi et al, 2017 ; Sharabi et al, 2016 ; Adam and Tatnall, 2017 ; Vasalou et al, 2017 ; Lambert and Dryer, 2018 ; Lipka et al, 2019 ; Ziadat, 2019 ), while others proposed a general reference to Special Educational Needs or used the World Health Organization definition of Disability ( World Health Organization, 2001 ; Berizzi et al, 2017 ; Naumova et al, 2017 ; García-González et al, 2020 ). Some papers reported the definition of LD based on international diagnostic criteria, others described specific national law/s or references ( Sharabi et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The papers showed a certain amount of heterogeneity in their definition of LDs. Some authors proposed a specific definition ( Chen et al, 2015 ; Richardson, 2015 ; Shonfeld and Ronen, 2015 ; Straub and Vasquez, 2015 ; Benmarrakchi et al, 2017 ; Sharabi et al, 2016 ; Adam and Tatnall, 2017 ; Vasalou et al, 2017 ; Lambert and Dryer, 2018 ; Lipka et al, 2019 ; Ziadat, 2019 ), while others proposed a general reference to Special Educational Needs or used the World Health Organization definition of Disability ( World Health Organization, 2001 ; Berizzi et al, 2017 ; Naumova et al, 2017 ; García-González et al, 2020 ). Some papers reported the definition of LD based on international diagnostic criteria, others described specific national law/s or references ( Sharabi et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, with regard to sample recruitment, some authors chose samples consisting of different groups of students with other kinds of disabilities and then specified the number of students with LDs ( Richardson, 2015 , 2016 ; Shonfeld and Ronen, 2015 ; Terras et al, 2015 ; Benmarrakchi et al, 2017 ; Sharabi et al, 2016 ; Alamri and Tyler-Wood, 2017 ; Berizzi et al, 2017 ; Kent et al, 2018 ; Lipka et al, 2019 ; Ouherrou et al, 2019 ; García-González et al, 2020 ); while in other papers, the sample is made up only of students with LDs ( Chen et al, 2015 ; Straub and Vasquez, 2015 ; Vasalou et al, 2017 ; Lambert and Dryer, 2018 ). Regarding the level of schooling, about 1/2 of the studies focused on University environments ( Richardson, 2015 , 2016 ; Terras et al, 2015 ; Alamri and Tyler-Wood, 2017 ; Naumova et al, 2017 ; Kent et al, 2018 ; García-González et al, 2020 ) and the other 1/2 examined primary and secondary schools ( Chen et al, 2015 ; Straub and Vasquez, 2015 ; Benmarrakchi et al, 2017 ; Rice and Carter, 2016 ; Smith et al, 2016 ; Adam and Tatnall, 2017 ; Berizzi et al, 2017 ; Vasalou et al, 2017 ; Baharuddin and Dalle, 2019 ; Lipka et al, 2019 ; Ouherrou et al, 2019 ; Ziadat, 2019 ; Nieto-Márquez et al, 2020 ). One paper focused on the transition from school to university ( Sharabi et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Research found that an effective way for teachers to use computer technology is to integrate technology in the curriculum. This helps students with special needs gain lifelong skills and boost their self-esteem and communication skills (Adam and Tatnall, 2017). (Russell, Bebell, O'Dwyer, et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Using computers in classrooms helps teachers to individualise instruction and introduce materials in more adaptive ways. The use of information and communication technology (ICT) enhances the independence of students with learning disabilities (LD) and provides them with appropriate skills that allow them to continue their study and move to normal work environment (Adam and Tatnall, ). Computers can be advantageous not only in the presentation of instructional content but also promote students’ interaction to the computer (Lewandowski, Wood and Miller, ).…”
Section: Introductionmentioning
confidence: 99%
“…Children must be prepared to acquire abilities and knowledge in the actual world and the application of technology in the learning environment will allow them to use their thinking abilities to reach social and emotional development [ 11 , 12 ]. Learning environments enriched with technology in its variety [ 13 , 14 ] will improve attention levels, motivation, knowledge and students’ abilities in a positive way, especially in children with language disorders and special education [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%